Reading the Bible intertextually - Hays, Richard B.; Alkier, Stefan; Huizenga, Leroy Andrew, 1974- (Waco, Tex. : Baylor University Press, 2009)
Even in an era of expanding methodologies for biblical studies, psalms study seems to be stuck in the old tracks of form criticism. While often beneficial, form criticism excludes two important ways of reading the psalms: that of reading the psalms with the narratives of the Hebrew Scriptures as the historical super-scriptions suggest, and that of a feminist reading by expanding an exclusive focus on the cult. This book looks to correct these problems by investigating the psalms via intertextual method, both by seeing the psalms as intertextual - made up of a multitude of other texts - and by reading the psalms intertextually with texts outside the psalms. This book also introduces the reader to the variety of intertextual theories in the literary guild and develops an intertextual hermeneutic of biblical study based on these theories that bridges the gap between literary theory and the practice of biblical interpretation. --From publisher's description.
Intertextuality and the semiotics of biblical texts / Stefan Alkier -- Intertextuality and historical approaches to the use of scripture in the New Testament / Steve Moyise -- How does God act? : intertextual readings of 1 Corinthians 10
Includes bibliographical references and index.
Keywords: Bible -- Criticism, Textual -- Congresses; Intertextuality in the Bible -- Congresses